CODE MIXING AS AN ANTI-POLITICAL INDISCRETION AMONG FARM LABORERS AT AJUNG, KALISAT, JEMBER - Yudistira, Riantino; Muta'allim, Muta'allim (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
One’s identity affects language production in the simplest form of communicational acts. The language serves dual purposes, conveying messages or as a vessel containing information about the speaker's socio-cultural identity. This research employed code-mixing acts constantly applied by farm laborers in their communication with land owners as the primary data to discover how the language codes were picked and arranged in excellent syntactical order to reflect meanings and metafunctions. The result of this research learned sensitive information on how politics allowed subjects equipped with the power to legitimate domination over the society and how the unbalanced rights and obligations were purposively maintained to suppress the farmers and their laborers to remain subordinated and weak subjects who lack resources.